Inclusion of the concepts of modern phisics in the classroom and the difficulties encountered by teachers - R. Amorim; O. Santos; A. R. Cruz; F. C. Santos (Scientific Electronic Archives, 2015)
In the study, we aimed to demonstrate through a literature review, the main obstacles that permeate the introduction of Modern Phisics by teachers. For this reason, if made necessary a analisys, in official documents on whichs guidelines they bring to teachers on how to work the content covering the Modern Physics and the importance of this study for the students and, in Physics textbook about the approach of this theme, it was found that this exists, but, in a very basic. With respect to the difficulties to teach Physics proved that these are the most varied possible, with emphasis on lack of necessary instruction during their academic training for the approach in the classroom and research into the teaching of Science that do not contribute to the teaching practice. To help teachers are presented some teaching methods with the purpose of promoting a learning significantly more of the concepts of Modern Physics.